2021
DOI: 10.3390/nano11051238
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene glycol)-Alendronate-Coated Magnetite Nanoparticles Do Not Alter Cardiovascular Functions and Red Blood Cells’ Properties in Hypertensive Rats

Abstract: In this study, magnetite nanoparticles were prepared and coated with poly(ethylene glycol) terminated by alendronate to ensure firm binding to the iron oxide surface. Magnetic nanoparticles, designated as magnetite coated with poly(ethylene glycol)-alendronate (Fe3O4@PEG-Ale), were characterized in terms of number-average (Dn) and hydrodynamic (Dh) size, ζ-potential, saturation magnetization, and composition. The effect of particles on blood pressure, vascular functions, nitric oxide (NO), and superoxide produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…On the other hand, acute intravenous administration of Fe 3 O 4 @PEG-Alendronate NPs to SHR rats did not produce changes in BP when investigated 100 min after acute i.v. infusion [ 36 ]. In this study, a decrease in BP occurred only in SHR 24 h post-treatment, suggesting possible changes in vascular functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, acute intravenous administration of Fe 3 O 4 @PEG-Alendronate NPs to SHR rats did not produce changes in BP when investigated 100 min after acute i.v. infusion [ 36 ]. In this study, a decrease in BP occurred only in SHR 24 h post-treatment, suggesting possible changes in vascular functions.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we found that an acutely infused lower dose of the USPIONs did not alter 5-HT-induced contractions and overall endothelium-dependent ACh-induced relaxations but elevated its NO-dependent component in WKY. Similarly, Fe 3 O 4 @PEG-alendronate-coated NPs did not damage the vascular function of the femoral artery in SHR after a single infusion [ 36 ]. In this study, 5-HT-induced contractions were unaltered by repeated USPION administration, while NA-induced contractions were significantly increased, compared to the control SHR, suggesting elevated sympathetic nervous system tone.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased uptake of USPIONs into erythrocytes of SHR could be one of the reasons why USPIONs had no effect in SHR animals [47]. Oleksa et al (2021) reported that administration of USPIONs had no effect on the fundamental properties and deformability of erythrocytes in SHR [12]. In the WKY group, acute stress and USPIONs significantly reduced antioxidant capacity in erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…USPIONs are coated with polyethylene glycol (PEG), which ensures their stability and biocompatibility, improves their distribution, and reduces their uptake by the mononuclear phagocytic system [10,11]. The PEG coating of USPIONs reduces undesired interactions with plasma proteins and their subsequent opsonization as well as allowing targeting ligands to be conjugated onto the USPIONs [4,12]. However, using different types of NPs/USPIONs in biomedical applications may cause problems related to their ability to increase oxidative stress and potential toxicity [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, IONPs have been widely applied in biomedicine and bioengineering such as drug delivery, imaging and cancer therapy. 15,55,56 Ferumoxytol, composed by an iron oxide core and a dextran (PSC) shell, is the only inorganic nanodrug approved by Food and Drug Administration (FDA) for clinical application in vivo. 31 Previously, we found that IONPs γ-Fe 2 O 3 @PSC with cellular uptake promoted the osteogenic differentiation of human bone-derived MSCs on the 2D cell culture platform.…”
mentioning
confidence: 99%